STRATEGIES AND DETERMINANTS INFLUENCING CERVICAL CANCER SCREENING PARTICIPATION: A NARRATIVE REVIEW OF GLOBAL EVIDENCE - Nanik Setiyawati; Sri Sulistyowati; Heru Priyanto (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Cervical cancer remains a leading cause of morbidity and mortality among women worldwide, particularly in low- and middle-income countries. Despite the availability of effective screening methods such as Pap smear and HPV testing, participation rates remain suboptimal due to various social, cultural, and systemic barriers. This study aims to identify effective strategies and key determinants influencing women’s participation in cervical cancer screening across diverse cultural and geographical contexts. A narrative synthesis of 12 peer-reviewed articles published between 2018 and 2025 was conducted. Articles were selected based on relevance to cervical cancer screening, including randomized controlled trials, cross-sectional surveys, systematic reviews, and meta-analyses. Key themes were extracted and analyzed for trends, effectiveness of interventions, and associated factors. Educational interventions, including empowerment programs and narrative media approaches, significantly increased screening knowledge and participation (p < 0.05). Opt-out invitation systems and community-based outreach campaigns demonstrated higher uptake compared with routine invitations. However, substantial gaps persist, particularly among rural and low-income women, due to limited awareness, fear, and cultural stigma. Factors such as education, income, age, parity, and contraceptive use were consistently associated with screening participation. The conclusion of this study is that integrated strategies combining education, community empowerment, and opt-out systems effectively enhance cervical cancer screening uptake. Addressing sociocultural and economic barriers through context-specific public health interventions is essential. Further longitudinal studies are needed to evaluate the sustainability of these approaches in improving screening behavior.